+0  
 
0
1116
2
avatar+1494 

solve this literal equation

nx+my=a

-nx+my=b

 Oct 4, 2017
 #1
avatar+1491 
0

What does it call to be solved for?

 Oct 4, 2017
 #2
avatar+124676 
+1

I am solving for x and y

 

nx+my = a

-nx+my = b        add the two equations  and we get

 

2my  =  a + b        divide both sides by 2m

 

y  =  (a + b) / (2m)

 

Put this back into the first equation for y

 

nx  +  m [ (a + b) / (2m)]  = a      simplify

 

nx +  (a + b) / 2    = a           subtract (a + b) / 2   from both sides

 

nx  =  a  -  (a + b) / 2         we can write this as

 

nx  =   [ 2a  - a - b ]  / 2

 

nx =  [ a - b] / 2       divide both sides by n

 

x =  ( a - b ) / (2n)

 

 

cool cool cool

 Oct 4, 2017

15 Online Users